Antiprotozoal and Cytotoxicity Assays of the Isolates of Tephrosia tinctoria - Ganapaty, S.; Lakshminarayana, K.; Lakshmi, P.; Steve Thomas, P. (Asian Journal of Chemistry, 2010)
The in vitro antiprotozoal assays of the flavonoids isolated from the roots of Tephrosia tinctoria, were studied for their potential to inhibit parasitic protozoa Trypanosoma, Leishmania and Plasmodium. The cytotoxicity of the flavonoid derivatives was performed using Cell line L-6 (rat skeletal muscle myoblasts). Of the three flavonoids studied, 2-hydroxy tephrosin and tephrinone exhibited moderate activity against both Trypanosoma brucei rhodensiense and T. cruzi, mild activity against Leishmania donovani and no activity against Plasmodium falciparum.